Corrigendum: Effects of 7-hydroxy-2-(4-hydroxy-3-methoxyphenyl)-chroman-4-one on serum levels of antioxidant enzymes in hyperlipidemic rats - Prasetyastuti, .; Gama, Noviyanty Indjar; Ayunda, Rahmah Dara (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2023)
-